2012
DOI: 10.1080/08873631.2012.646890
|View full text |Cite
|
Sign up to set email alerts
|

Telling stories in, through and with Country: engaging with Indigenous and more-than-human methodologies at Bawaka, NE Australia

Abstract: Recent work in ethnographic and qualitative methods highlights the limitations of academic accounts of research interactions that aim for total objectivity and authority. Efforts to move beyond totalizing accounts of both the research experience and the investigator raise questions of how to engage with, make sense of, and (re)present embodied, sensual, visceral, and the ultimately placed qualities of collaborative research interactions. Our response to this set of questions entailed recognizing and respecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 39 publications
(36 reference statements)
1
87
0
Order By: Relevance
“…This reflection should be combined with conversations with community members and collaborators to determine methods and frameworks that prioritize Indigenous ways of knowing throughout all stages of the project. One can utilize various narrative methods, such as storytelling (Wright et al, 2012), talking circles (Hoazous et al, 2010), the conversational method (Kovach, 2010) and yarning (Geia et al, 2013). Others methods are specific to communities or cultures, and thus difficult to generalize appropriately, such as the Anishnaabe Symbol-Based Reflection (Lavallée, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflection should be combined with conversations with community members and collaborators to determine methods and frameworks that prioritize Indigenous ways of knowing throughout all stages of the project. One can utilize various narrative methods, such as storytelling (Wright et al, 2012), talking circles (Hoazous et al, 2010), the conversational method (Kovach, 2010) and yarning (Geia et al, 2013). Others methods are specific to communities or cultures, and thus difficult to generalize appropriately, such as the Anishnaabe Symbol-Based Reflection (Lavallée, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Storytelling is a qualitative research method, in that participants describe their answers orally rather than on questionnaires, although the relationship and co-creation between the researcher and participant or a group of participants is also considered (Dyll-Myklebust, 2014;Hall et al, 2015;Roe et al, 2012;Wright et al, 2012). Wright et al (2012) indicated that storytelling was the ideal method for integrating nonhuman elements (e.g., animals, water, wind) into their data collection and analysis. Storytelling can also be useful in the dissemination of knowledge uncovered in the data collection and/or analysis phases.…”
Section: Storytellingmentioning
confidence: 99%
“…(Mowaljarlai & Malnic, 1993, p. 87) Patience was crucial to my research practice, as was being open to learning in ways that I had never before imagined: through dreams (Turner, 2010), liyan (feeling and intuition) (Roe & Hoogland, 1999) and allowing things to be revealed by County rather than 'discovered' (Graham, 2009). Doing ontologically open research forced me to de-centre the human as the primary source and holder of knowledge (Graham, 2009;Rose, 1988) and acknowledge the agency of Country to 'share' knowledge embodied within the land (Graham, 2009;Guyula, 2010;Turner, 2010;Wright et al, 2012). Hence, practicing ontological openness led to not only a recognition of Indigenous forms of knowledge production, but also the performance of such methods; it enabled me to know with Country.…”
Section: Creating a Methodology For Ontological Opennessmentioning
confidence: 99%
“…Yet, which categories and metaphors would I use to render visible the realities that others and I were performing? Wright et al (2012) also questioned the ontological limitations of attempting to describe human connections with the land and the agency of Country merely through Western categories. What I was coming to see was that 'to describe the real is always an ethically charged act' (Law, 2009, p. 155).…”
Section: Creating a Methodology For Ontological Opennessmentioning
confidence: 99%
“…The authors of this article are both Yolŋu and non-Yolŋu. We have worked together as part of an innovative 9 year Indigenousacademic research collaboration that has focused on communicating Indigenous Yolŋu knowledge to non-Indigenous people (Bawaka Country including Wright et al, 2015;Burarrwanga, Ganambarr et al, 2013;Burarrwanga, Maymuru et al, 2012;Lloyd, Wright, Suchet-Pearson, Burarrwanga, & Bawaka Country, 2012;Suchet-Pearson, Wright, Lloyd, Burarrwanga, & Hodge, 2013;. One aspect of this work has been looking at the role of the tourism business in achieving this objective (Wright, Suchet-Pearson, Lloyd, Burarrwanga, & Burarrwanga, 2009).…”
Section: Transforming Tourists and "Culturalising Commerce": Indigenomentioning
confidence: 99%